Persuasive Messages Through TikTok Social Media @Pandawara in Raising Awareness of Environmental Issues - Rahmawati, Ilfa Husnia; Suwitno, Bangbang; Nurfalah, Farida (Indonesian Journal of Advanced Research, 2025)
Social media has become an effective tool in shaping public opinion, including environmental awareness. This study aims to examine the persuasive communication of the TikTok account @Pandawara in enhancing followers' understanding of environmental issues. Using persuasive theory and a qualitative descriptive approach, data were collected through interviews and observations. The results indicate that short videos with educational and inspirational messages without blaming specific parties successfully attract attention and build environmental awareness. The @Pandawara digital campaign also encourages attitude changes and active participation in maintaining environmental cleanliness. TikTok has proven to be an effective communication tool for spreading environmental messages and driving social action.